The budget control in the function of the civil and democratic control of the armed forces in the Republic of Serbia - Knežević Milena; Nikolić Srboljub; Neševski Aleksandar (Војно дело, 2021)
One of the important indicators of democratization of each society is the constitutional and legal definition of the role of the military and the possibility of its control. The civil and democratic control of the Serbian Armed Forces primarily includes control of the use and development of the Serbian Armed Forces, internal and external control of the expenditures for the military needs, monitoring and informing the public about the state of preparations of the Armed Forces, providing free access to information of public importance and defining responsibilities for performing the military duties in accordance with the law. The instrument for financing the military expenditures in the Republic of Serbia is the state budget. During the drafting of the Law on Budget, the costs for the military needs are planned for the budget year and the following two years. Having in mind that the Law on Budget is passed by the highest legislative body - the National Assembly, the main principle of the democratic control of the military expenditure planning is provided. However, the budget execution implies the control over the use of the budget funds, whereby the Law on Budget System provides for several levels of control, organized as internal and external control. The internal control of the military expenditures, expressed in the budget of the Republic of Serbia, is carried out by the financial service bodies of the units and institutions of the Serbian Armed Forces, the Accounting Centre of the Budget and Finance Sector of the Ministry of Defence, the Defence Inspectorate, the Military Security Agency, the Criminal Investigation Group and the Internal Audit of the Ministry of Defence. The external control of the budget intended for the military needs is performed by the State Audit Institution and the Budget Inspection. The objective of the control is to determine whether the actions of the Serbian Armed Forces are in accordance with the position stipulated by the Constitution, as well as with the policy that the mentioned representative and executive authorities define in their acts.